The impact of displacement on disabled, injured and older Syrian refugees - Skinner, M (Refugee Studies Centre, University of Oxford, 2014)
In contexts of displacement it is critical to recognise that some groups in the population may require specific attention. Awareness of these needs has major consequences for the types of services required, and the way they are delivered.